Essential Oil Composition and Bioactive Properties of Lemon Balm Aerial Parts as Affected by Cropping System and Irrigation Regime - Chrysargyris, Antonios; Petropoulos, Spyridon A.; Tzortzakis, Nikos G. (My University, 2022)
The ongoing climate crisis necessitates the sustainable use of natural resources and the adop-tion of environmentally friendly agronomic practices. Deficit irrigation is an ecofriendly technique that allows for the improvement in the water use efficiency of crops. On the other hand, medicinal and aromatic crops, which usually have an innate tolerance to harsh conditions, are suitable candidates for cultivation under low-input cropping systems. In the present study, Melissa officinalis plants were cultivated under conventional and organic cropping systems, while in each system two irrigation regimes (full irrigation or deficit irrigation) were tested. The aerial parts of the plants were evaluated in terms of growth and physiological parameters, chemical composition, antioxidant activity, essential oil yield and essential oil composition. Our results indicate that prolonged water stress after two deficit irrigation cycles had detrimental effects on the plant growth and biomass production, whereas it significantly increased the essential oil yield, regardless of the cropping system (organic or conventional cultivation). The recorded physiological parameters are in agreement with morphological features, especially the stomatal conductance, which was significantly reduced under deficit irrigation for both cultivation systems, revealing that the growth inhibition was the result of stomatal closure and carbon dioxide deprivation. Deficit irrigation and organic cultivation also increased total phenol and total flavonoid content, especially in the second harvest, thus resulting in higher antioxidant activity assayed by the FRAP method. In contrast, DPPH and ABTS methods did not show any differences among the tested treatments in the second harvest, which suggests that other bioactive compounds are also involved in the overall antioxidant mechanism of lemon balm plants, as indicated by the increased ascorbic acid content. Regarding the essential oil composition, the major detected compounds were geranial and neral and, although they were both increased under the organic cropping in the first harvest, the same trend was not observed in the second harvest. Finally, a variable effect of cropping system and irrigation regime on minerals content was recorded. In conclusion, deficit irrigation is an ecofriendly practice that could be applied in conventional and organic cropping systems of lemon balm crops, aiming to reduce irrigation water consumption and compensate for reduced herb yields with increased essential oil yield and polyphenol content.
Keywords: Melissa officinalis; Organic cultivation; Water deficit; Essential oils; Volatile compounds; Antioxidant activity; Nutrient content